Characterization of Magnesium Doped Lithium Iron Silicate - Juan A. Jaén; Josefina Iglesias; Alcides Muñoz; Jesús A. Tabares; Germán A. Pérez Alcázar (Croatica Chemica Acta, 2015)
The synthesis of Mg doped Li2Fe1–xMgxSiO4 (x = 0, 0.10 and 0.15) via solid-state reaction is reported. The product was characterized by Mössbauer spectroscopy (MS), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), magnetic measurements and scanning electron microscopy (SEM). The structures of the reaction products were confirmed to be the monoclinic structure P21/n, but impurities were detected in them. In the undoped sample small amounts of lithium iron oxide or lithiated magnetite was obtained, whereas a magnetic phase was found in samples with more than 10 % (mole fraction) of Mg doping.